2019
DOI: 10.1007/s11128-018-2161-x
|View full text |Cite
|
Sign up to set email alerts
|

Sharing of tripartite nonlocality by multiple observers measuring sequentially at one side

Abstract: Standard tripartite nonlocality and genuine tripartite nonlocality can be detected by the violations of Mermin inequality and Svetlichny inequality, respectively. Since tripartite quantum nonlocality has novel applications in quantum information and quantum computation, it is important to investigate whether more than three observers can share tripartite nonlocality, simultaneously. In the present study we answer this question in the affirmative. In particular, we consider a scenario where three spin-1 2 parti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 59 publications
1
34
1
Order By: Relevance
“…Let us comment on that point. Previously, in the non-anonymous case, the same scaling was obtained for all measurements and CSMUB (see Eqs (18) and (26)), as the proofs relied only on the fact that p iso steer tends to 0 when d goes to infinity. In the scenario we are now considering, as fewer assumptions are needed, the scaling depends on the precise behavior of p iso steer (d).…”
Section: Anonymous Sequential Steeringmentioning
confidence: 66%
See 1 more Smart Citation
“…Let us comment on that point. Previously, in the non-anonymous case, the same scaling was obtained for all measurements and CSMUB (see Eqs (18) and (26)), as the proofs relied only on the fact that p iso steer tends to 0 when d goes to infinity. In the scenario we are now considering, as fewer assumptions are needed, the scaling depends on the precise behavior of p iso steer (d).…”
Section: Anonymous Sequential Steeringmentioning
confidence: 66%
“…This motivated further work exploring the potential of these ideas for randomness generation [13] and their classical communication cost [14], and led to experimental demonstrations [15,16]. More recently, these ideas were extended to other types of quantum correlations [17][18][19]. Specifically, Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Since the presence of non-locality implies the possibility of steering and the presence of entanglement, our work shows that it is also possible to achieve both of these with arbitrarily many independent Bobs using only a single pair of entangled qubits. This goes against some of the results in [18,22,23], and suggests that it is worth rethinking others that study the space of such correlations [24] or look at other Bell in-equalities [25] or more parties [26,27] after removing the assumption that both measurements used by each party have the same sharpness.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, a surprising result was reported by Silva et al that the number of observers sharing non-locality can be increased if the sequential weak (unsharp) measurement was employed, where the non-signaling condition is dropped [27]. Their result later is confirmed by theoretical [28][29][30] as well as experimental works [31,32], and the sequential unsharp measurement strategy has been extended to study other types of quantum correlation [33][34][35]. It has shown that the maximum number of Alices who can simultaneously share steering with a single Bob can also beat the steering monogamy limits [36][37][38].…”
Section: Introductionmentioning
confidence: 96%